2015
DOI: 10.1007/s00726-015-2076-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an ultra-performance liquid chromatography quadrupole time of flight mass spectrometry method for rapid quantification of free amino acids in human urine

Abstract: An ultra-performance liquid chromatography quadrupole time of flight mass spectrometry (UPLC-qTOF-MS) method using hydrophilic interaction liquid chromatography was developed and validated for simultaneous quantification of 18 free amino acids in urine with a total acquisition time including the column re-equilibration of less than 18 min per sample. This method involves simple sample preparation steps which consisted of 15 times dilution with acetonitrile to give a final composition of 25 % aqueous and 75 % a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 49 publications
0
33
0
Order By: Relevance
“…Recently, an ultra performance liquid chromatography‐electrospray ionisation‐time of flight mass spectrometry (UPLC‐ESI‐QTOFMS) urine metabolomic survey found that eight potential biomarkers associated with tryptophan, pantothenic acid and porphyrin were related to triptolide toxicity and licorice had potential protective therapeutic effects against such toxicity (Wang et al, ). Since many endogenous metabolites are highly polar molecules, the application of UPLC‐ESI‐QTOFMS using hydrophilic hydrophilic interaction chromatography (HILIC) chromatography can improve the retention of polar metabolites (Joyce et al, ) and provide a relatively comprehensive separation method for the analysis of biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an ultra performance liquid chromatography‐electrospray ionisation‐time of flight mass spectrometry (UPLC‐ESI‐QTOFMS) urine metabolomic survey found that eight potential biomarkers associated with tryptophan, pantothenic acid and porphyrin were related to triptolide toxicity and licorice had potential protective therapeutic effects against such toxicity (Wang et al, ). Since many endogenous metabolites are highly polar molecules, the application of UPLC‐ESI‐QTOFMS using hydrophilic hydrophilic interaction chromatography (HILIC) chromatography can improve the retention of polar metabolites (Joyce et al, ) and provide a relatively comprehensive separation method for the analysis of biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, because of the weak light-absorptive property of amino acids, pre-or post-column derivatization with an appropriate labeling reagent is performed for determining amino acids with sensitivity and selectivity in HPLC with UV detection (HPLC-UV) and fluorescence detection (HPLC-FL) systems [9,10]. Recently, many LC with mass spectrometric detection methods such as LC-MS/MS and LC-qTOF-MS/MS have been proposed [11][12][13], and these methods are applied to the carrying out of metabolism studies and diagnosis based on amino acids profiles [13][14][15][16]. Electrochemical detection generally has the following merits: an electrochemical detector is inexpensive compared with a spectrometric detector, electrochemical devices, including electrodes, can be easily minimalized to develop a portable sensor with simple procedures, and a low energy requirement that can be used either in laboratory or for on-site measurements [22].…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid analysis is an important technique in many pharmaceutical, medical, chemical, food research, and industrial areas [1][2][3]. Thus far, various analytical methods have been proposed to determine amino acids, including high-performance liquid chromatography, capillary electrophoresis, enzyme assay, and chemical sensors [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Usually, because of the weak light-absorptive property of amino acids, pre-or post-column derivatization with an appropriate labeling reagent is performed for determining amino acids with sensitivity and selectivity in HPLC with UV detection (HPLC-UV) and fluorescence detection (HPLC-FL) systems [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, HILIC was widely used to analyze highly polar constituents, including monoamines, amino acids and peptides as well as many other biologically important compounds in complex biological matrices without the need for derivatization or ion‐paring agents (Chen et al, ; Guo et al, ; Lai, Kline, & Wang, ; Wu et al, ). For example, HILIC–MS/MS analysis of human urine was utilized by Richard Joyce et al, which quantified 18 AAs using 18 stable isotope internal standards in <18 min (Joyce et al, ). Prinsen et al quantified 36 AAs (24 quantitative/12 qualitative) in plasma in a single MS run of 18 min (Prinsen et al, ).…”
Section: Introductionmentioning
confidence: 99%